MODEL PERKEMBANGAN PENYAKIT BULAI DENGAN VARIABEL BUDIDAYA DI KECAMATAN PURI KABUPATEN MOJOKERTO - Nindias Oktavia Wulandari; Herry Nirwanto; Wiwik Sri Harijani; Latief Imanadi (UPN VETERAN JAWA TIMUR, 2020)
Downy mildew is a major disease in maize plants in Indonesia. It was reported that yield losses due to downy mildew ranged from 50%-80% in some areas of maize production center. Efforts are made to control downy mildew disease by conducting tillage, crop rotation, intercropping, use of fungicides, and irrigation affect the development of downy mildew. Therefore, efforts to deterimine the most effective control of downy mildew need to be carried out more extensive research, one of which is by looking at the downy mildew development models based on different cultivation variables that aim to find out the variables that influence the high and low incidence of downy mildew in Mojokerto. the results show that the model that is able to represent the development of downy mildew in Mojokerto was monomolecular. The incidence of the disease using varieties P35, NK 7328, NK 6172, NK 212 shows the category of mild attacks and varieties of Bisi 18 shows the category moderate attacks. Tillage is a way of cultivation that influences the low incidence and infection rate of downy mildew in Puri, Mojokerto.